Study on the heating characteristics of microwave double resonators under uniform radiation - Shuqiao Wang; Mengfei Han; Chandrasekar Srinivasakannan; Jingzhou Yuan; Jinghan Guo; Yaxian Geng; Xin Wang (Case Studies in Thermal Engineering, 2023)
Microwave heating are generally performed in the device with a square resonant cavity, rather than a cylindrical resonant cavity, under the frequency of 2.45 GHz. In this study, a frequency variable microwave heating device with square and cylindrical resonant cavities was developed and applied to assess the heat characteristics of SiC. A simulation model based on the experimental setup was developed, and the Spearman correlation coefficients between the calculated and the measured data were 0.78 for the circular resonant cavity and 0.85 for the square resonant cavity. The results indicate that within the entire frequency range, the calculated and measured temperature in a circular resonant cavity could reach a maximum of 96.5 °C and 77.5 °C, respectively, while in a square resonant cavity, only 53.8 °C and 50.5 °C, respectively. Moreover, SiC square slice exhibit better heating characteristics than disc, and the temperature increases with increase in thickness. The orientation of SiC towards the incident port was also found to influence the heating characteristics. This result provides a theoretical basis for the development of cylindrical microwave heating devices.